Clinical audit for first-trimester ultrasound screening: a single center experience - Wu, Xining; Zhang, Yixiu; Meng, Hua; Ouyang, Yunshu; Xu, Zhonghui; Dai, Qing; Zhang, Peipei (Frontiers in Medicine, 2025)
ObjectiveThe purpose of this study was to assess the quality of 11–14-week fetal ultrasound images and physician scanning performance in a large general hospital to inform future quality improvement initiatives.MethodsA retrospective audit of ultrasound scans of normal fetuses at 11–14 weeks was conducted from November 2021 to March 2023 at a large tertiary general hospital in Beijing, China. Ten anatomical views were analyzed by two experienced assessors. Scan completeness and view completeness rates ≥ 70%, and logbook quality scores ≥ 42 (i.e., ≥ 70% of the maximum possible score), were considered acceptable.ResultsThe overall scan completeness of 256 logbooks was 77.4%. The scan completeness of 189 logbooks (73.8%) was acceptable. The median image quality score for the 256 logbooks was 37 (interquartile range, 28–46), and 96 logbooks (37.5%) had acceptable image quality, with a score ≥ 42. The scan completeness of 23 sonographers (63.9%) was > 70%. Sonographers with intermediate titles performed a higher average number of fetal ultrasound scans than those with senior titles (148 vs. 115 scans), and their scan completeness and logbook image quality scores were also superior (87% vs. 69% and 43.24 ± 6.38 vs. 31.62 ± 11.28, respectively; both p < 0.05).ConclusionThe majority of sonographers met the expectations of the audit. Sonographers performing more fetal ultrasound scans may have an advantage in terms of scan completeness and image quality.